Guidelines for enteral nutrition in infants born preterm: 2023 update by the Portuguese Neonatal Society. Part I. Nutrient requirements and enteral feeding approach during the hospital stay - Luís Pereira-; Susana Pissarra; António Gomes; Rosalina Barroso; Cláudia Fernandes; Daniel Virella; Israel Macedo; Edmundo Santos; Andreia Teles; Manuela Cardoso (Publicaciones Permanyer, 2023)
Recent evidence-based data motivated this update of the Portuguese Neonatal Society guidelines for the enteral nutrition of infants born preterm. The purpose of this document is to support the clinical practice and was mainly oriented by the updated European Society for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) 2022 position paper, the World Health Organization recommendations 2022, and other reference articles, particularly systematic reviews. These guidelines are published in two parts. Part I addresses the nutrient requirements and the enteral feeding approach during the hospital stay, including optimization of the mother's own milk feeding and methods for enteral feeding. Part II is directed to particularities of enteral feeding in specific clinical conditions, and feeding after discharge, including breastmilk fortification at home and introduction of complementary feeding.